2017
DOI: 10.17705/1cais.04131
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual Model for User-System Collaboration: Enhancing Usability of Complex Information Systems

Abstract: Abstract:A variety of organizations around the world use complex information systems (e.g., enterprise resource planning and supply chain management systems). However, poor usability caused by system complexity continues to frustrate users and damage the reputation of these systems. In this study, we address usability issues with complex information systems from the human-computer collaboration perspective by modeling user-system interaction as a joint activity between the system and its users. We propose a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…Taking a STS perspective on HMC [58,61,67] in a complex decision-making context, we set out to explore the symbiotic relationship between human and technology. We found that there are three facets of symbiotic co-evolution: agents' evolution, activity evolution, and structural evolution (see Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Taking a STS perspective on HMC [58,61,67] in a complex decision-making context, we set out to explore the symbiotic relationship between human and technology. We found that there are three facets of symbiotic co-evolution: agents' evolution, activity evolution, and structural evolution (see Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Adaptation and learning. As other authors have already mentioned [67], HMC is not a one-time event but a new way of using and perceiving machines. In the context of this new relationship, intensive cooperation leads to mutual learning and adaptation among collaborators.…”
Section: Division Of Labormentioning
confidence: 97%
See 3 more Smart Citations